Temperature determines the diversity and structure of N2O‐reducing microbial assemblages. (24th March 2018) - Wu, Bo; Liu, Feifei; Weiser, Michael D.; Ning, Daliang; Okie, Jordan G.; Shen, Lina; Li, Juan; Chai, Benli; Deng, Ye; Feng, Kai; Wu, Liyou; Chen, Shouwen; et al.
Abstract: Micro‐organisms harbouring the nosZ gene convert N2 O to N2 and play a critical role in reducing global N2 O emissions. As higher denitrifier diversity can result in higher denitrification rates, here we aimed to understand the diversity, composition and spatial structure of N2 O‐reducing microbial assemblages in forest soils across a large latitudinal and temperature gradient. We sequenced nosZ gene amplicons of 126 soil samples from six forests with mean annual soil temperatures (MAST) ranging from 3.7 to 25.3°C and tested predictions of the metabolic theory of ecology (MTE) and metabolic‐niche theory (MNT). As predicted, α‐diversity of nosZ communities increased with increasing MAST, within‐site β‐diversity decreased and two (pH and soil moisture) of the three niche widths examined were larger with increasing MAST. We calculated β‐nearest taxon distance and Raup–Crick metric to quantify the relative influence of the assembly processes determining nosZ assemblage structure. Environmental selection was the primary process driving assemblage structure in all six forests. Homogenizing dispersal was also important at one site, which could be explained by the site's much lower variability in soil chemistry. We used canonical correspondence analysis and multiple regression on matrices to examine relationships between nosZ communities and environmental factors, and found that temperature and spatial distance were significant predictors of nosZ assemblage structure. Overall our results support both theories (MTE and MNT) tested, showing that higher temperatures are correlated with higher local diversity, wider niche breadths and lower within‐site turnover rates. A plain language summary is available for this article. Abstract : Plain Language Summary